Performance comparison of voltage stability indices for weak bus identification in power systems - Verayiah R.; Mohamed A.; Shareef H.; Abidin I.H.Z. (Institute of Physics Publishing, 2023)
Voltage collapse event is identified as complex and localized in nature but its effect is extensive once occurred. The vital effect of voltage collapse would be the total system collapse or blackouts which would cost a large loss to utility companies. Eventually, on- line monitoring of power system stability has become an important factor for electric power utilities. The last utmost option to avert voltage collapse incident from occurring is by the implementation of under voltage load shedding scheme. The identification of location for load shedding is the main motivation of the study. The weakest bus in a power system is identified as the location for load shedding. This location is obtained using voltage stability index Ld. The performance and effectiveness of Ld index is compared with Fast Voltage Stability Index (FVSI) and Le Index. The results obtained indicate that Ld Index can be used to identify the weak bus in a power system and consequently for the placement of UVLS relays in a power system network. Published under licence by IOP Publishing Ltd.